Cardiovascular Complications in Community-acquired Pneumonia. Issue 2 (March 2015) - Krüger, Stefan; Frechen, Dirk
Abstract : Cardiovascular complications and comorbidities in community-acquired pneumonia (CAP) are very frequent. Therefore clinicians must see CAP not as a simple infectious accident. They should look at CAP patients as high-risk cardiovascular patients and have to diagnose and treat them in an appropriate way. Cardiac complications in the acute phase of CAP are most often seen in the first days of disease. Therefore, better monitoring, diagnostics, and risk stratification in CAP with respect to cardiovascular diseases should be established. There is a long-term higher risk for cardiovascular events and mortality in CAP patients that has not been adequately recognized. Cardiovascular morbidity and mortality, especially in patients with known cardiovascular disease, might be reduced by influenza and pneumococcal vaccination.